THE CONTRIBUTION OF THE FIRST PRINCIPLE OF PANCASILA TO THE FORMATION OF MODERATE RELIGIOUS CHARACTER IN THE DISRUPTION ERA - Aris Suhendar; Krissi Wahyuni Saragih (Program Pascasarjana UIN Sumatera Utara, 2025)
This study examines the contribution of the first principle of Pancasila to the formation of moderate religious character among youth in the era of digital disruption. The growing phenomenon of religion-based intolerance in digital spaces serves as a significant background for this inquiry. The aim of the research is to evaluate the extent to which the value of Belief in One Supreme God can be internalized within education and religious social life. The method employed is a meta-analysis literature review by analyzing academic studies from the past five years. Data were collected through systematic searches of reputable journals and analyzed using content analysis techniques and bibliometric visualization. The findings indicate that the value of divinity holds great potential in shaping tolerant religiosity, yet its implementation remains suboptimal. This study recommends the strategic integration of divine values into curricula and digital religious literacy initiatives.